Proposals for Improving the Technical State of Turbogenerators in Excess of the Service Life - Shevchenko, V. V. (Kremenchuk Mykhailo Ostrohradskyi National Universityrs, 2017)
The state of the world economy, the global economic crisis determined that the first priority in making engineering decisions is economic profitability. This affected on the state and development of the electric power industry, in particular, on the operational policy of repairs and the implementation of replacement schedules for turbogenerators that have fulfilled the service life. Therefore, the main worldwide trend of the development of energy systems and turbine generators was not the replacement of equipment that had worked its life, but the extension of the terms of his work.
Keywords: turbogenerator; reliability; extended life; stator core